Outcomes of endovascular repair of infrarenal penetrating aortic ulcers: insights from the abdominal aortic aneurysm registry of the German Institute for Vascular Research - Hatzl, Johannes; Behrendt, Christian-Alexander; Schmitz-Rixen, Thomas; Grundmann, Reinhart Thomas; Steinbauer, Markus; Böckler, Dittmar; Uhl, Christian (Vasa, 2023)
Background: To report technical success as well as perioperative outcomes of patients who underwent endovascular aortic repair (EVAR) of penetrating abdominal aortic ulcers ≤35 mm in diameter (PAU). Patients and methods: The abdominal aortic aneurysm (AAA) quality registry of the German institute for vascular research (DIGG) was used to identify patients with standard EVAR for infrarenal PAU ≤35 mm between 1/1/2019 and 12/31/2021. Infectious, traumatic, inflammatory PAUs, PAUs associated with connective tissue disease, PAUs following aortic dissection as well as true aneurysms were excluded. Demographics, cardiovascular comorbidity, technical success as well as perioperative morbidity and mortality were determined. Results: Amongst 11 537 patients who underwent EVAR during the study period, 405 with PAU ≤35 mm were eligible from 95 participating hospitals across Germany (22% women, 20.5% octogenarians). The median aortic diameter was 30 mm (Interquartile range 27-33). Cardiovascular comorbidities were frequent with coronary artery disease (34.8%), chronic heart failure (30.9%), history of myocardial infarction (19.8%), hypertension (76.8%), diabetes (21.7%), smoking (20.8%), history of stroke (9.4%), symptomatic lower extremity peripheral arterial disease (20%), chronic kidney disease (10.4%) and chronic obstructive pulmonary disease (9.6%). Most patients were asymptomatic (89.9%). Among the symptomatic patients, 13 presented with distal embolization (3.2%) and 3 with contained ruptures (0.7%). Technical success of endovascular repair was 98.3%. Both, percutaneous (37.1%) or femoral cut-down access approaches (58.5%) were registered. Endoleaks of any type were present with type 1 (0.5%), type 2 (6.4%) and type 3 (0.3%) endoleaks. Overall mortality was 0.5%. Perioperative complications occurred in 12 patients (3.0%). Conclusions: According to this registry data, endovascular repair of PAU is technically feasible with acceptable perioperative outcomes, but further studies investigating mid- and long-term data are needed before invasive treatment of PAU disease in an elderly and comorbid patient population should be recommended.
Online veröffentlicht: 7. März 2023
Gesehen am 19.07.2024